Restored allegorical figure - Ghosh, Ayan (Jio Institute, 2023)
Over time, these figures had dilapidated and suffered damage from exposure. In this statue, for example, the left hand was missing. During its restoration, the missing hand was re-modelled after careful study of old photographs. Craftsmen made replicas from Porbandar stone, and the hand was fixed using stainless steel.